Pengaruh Literasi Keuangan Dan Strategi Bisnis Terhadap Kinerja Usaha Mikro Kecil - Zulfikry Sukarno; Muhammad Umar Data (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The purpose of the study was to determine the effect of financial literacy on business strategy and performance of MSMEs in Makassar City. As for Financial Literacy as an independent variable, business performance as the dependent variable and business strategy as a mediating variable. The study used a descriptive quantitative approach using secondary data, namely by distributing questionnaires to 125 micro, small and medium enterprises in Makassar City. Data on MSME were obtained from the Makassar Cooperative and MSME Service. With non-probability purposive accidental sampling method. The research data was processed using SPSS 23 statistical software by performing the classical assumption test (normality test, multicollinearity test, heteroscedasticity test) which was then analyzed by multiple regression and descriptive analysis, then the research hypothesis was partially tested and the coefficient of determination was tested. The results of this study are financial literacy has a positive and significant effect on business strategy and business performance. Revealing that with good financial literacy, MSME actors will carry out the right business strategy and with every increase in financial literacy for MSME actors it will also improve their business performance. And the results of the mediation of the business strategy variable show that with financial literacy, MSME actors will carry out business strategies that result in better business performance